Future Land-Use Changes and the Potential for Novelty in Ecosystems of the United States - Martinuzzi, Sebastián; Gavier Pizarro, Gregorio Ignacio; Lugo, Ariel E.; Radeloff, Volker C. (2018)
Rapid global changes due to changing land use, climate, and non-native species are altering environmental conditions, resulting in more novel communities with unprecedented species combinations. Understanding how future anthropogenic changes may affect novelty in ecosystems is important to advance environmental management and ecological research in the Anthropocene. The main goal of this study was to understand how alternative scenarios of future land-use change may affect novelty in ecosystems throughout the conterminous United States. We used five spatially explicit scenarios of future land-use changes, reflecting different land-use policies and changes in agricultural markets, to quantify and map potential drivers of novelty. Our results showed large areas where future land-use changes may increase novelty in ecosystems. The major land-use changes known to increase novelty, including land abandonment and land-use expansion, were widespread in all scenarios (73 million to 95 million ha), especially in the eastern U.S. and along the West Coast. Our scenarios revealed that, at broad scales, future land-use changes will increase novelty in ecosystems, and that traditional conservation policies may have limited ability to prevent the process. In places such as the eastern U.S., conserving and maintaining historical conditions and associated biological diversity may become increasingly difficult due to future land-use changes and related ecological factors. Successful biodiversity conservation and environmental management in the Anthropocene will require novel conservation approaches to be relevant in areas with high levels of novelty in ecosystems.